2017
DOI: 10.1111/1756-185x.13038
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adiponectin and visfatin levels in rheumatoid arthritis and their correlation with disease activity: A meta‐analysis

Abstract: Our meta-analysis demonstrated that circulating adiponectin levels were significantly higher in patients with RA than in controls. Circulating visfatin levels were significantly higher in patients with RA than in controls and a positive correlation between circulating visfatin level and RA activity is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 36 publications
5
84
0
3
Order By: Relevance
“…In vivo studies on APN KO mice confirmed that Adiponectin has immunosuppressive effects since these animals present an increase of anti-inflammatory cells and mediators as well as an alteration of M1 (increased TNF-α, and IL-6), and M2 markers, (decreased IL-10) (Ohashi et al, 2010). Finally, human studies have demonstrated a strong modulation of Adiponectin serum concentrations and its receptors in course of immune disorders, powerfully suggesting that Adiponectin has an active role in regulating immune responses (Çoban et al, 2017;Dini et al, 2017;Pecoraro et al, 2017;Lee and Bae, 2018;Polito et al, 2019). Furthermore, it is able to acts also in oxidative stress, indeed Adiponectin in a cancer cells model induces apoptosis and reduce proliferation by oxidative stress in a time-and dose-dependent manner (Van Brocklyn and Williams, 2012).…”
Section: Adiponectin Functionsmentioning
confidence: 74%
“…In vivo studies on APN KO mice confirmed that Adiponectin has immunosuppressive effects since these animals present an increase of anti-inflammatory cells and mediators as well as an alteration of M1 (increased TNF-α, and IL-6), and M2 markers, (decreased IL-10) (Ohashi et al, 2010). Finally, human studies have demonstrated a strong modulation of Adiponectin serum concentrations and its receptors in course of immune disorders, powerfully suggesting that Adiponectin has an active role in regulating immune responses (Çoban et al, 2017;Dini et al, 2017;Pecoraro et al, 2017;Lee and Bae, 2018;Polito et al, 2019). Furthermore, it is able to acts also in oxidative stress, indeed Adiponectin in a cancer cells model induces apoptosis and reduce proliferation by oxidative stress in a time-and dose-dependent manner (Van Brocklyn and Williams, 2012).…”
Section: Adiponectin Functionsmentioning
confidence: 74%
“…A large number of observational epidemiological studies have been undertaken to investigate the role of adipokines in the occurrence and progression of RA. Two recent meta-analyses of case-control studies demonstrated that circulating adiponectin levels could be signi cantly higher in the RA patients than those in the health controls [30,31]. However, it was also reported separately that adiponectin levels were not related to RA activity [30,32].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent meta-analyses of case-control studies demonstrated that circulating adiponectin levels could be signi cantly higher in the RA patients than those in the health controls [30,31]. However, it was also reported separately that adiponectin levels were not related to RA activity [30,32]. Meanwhile, the ndings from meta-analyses consistently indicated that patients with RA may have higher circulating leptin levels compared with the control group [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of adipokines induced-ADAMTS gene expression in chondrocytes and chondrosarcoma was demonstrated before by our group (21-23). An up-regulated adiponectin level in both RA and OA patients was reported (24,25). After these fi ndings, the researchers have focused on the mechanism of adiponectin caused joint destruction.…”
Section: Discussionmentioning
confidence: 99%